The Influence of Pharmaceutical Service Quality on Outpatient General Patient Satisfaction at the Level IV 01.07.01 Military Hospital Pematangsiantar - Novi Wulandari Purba; Bunga Mas Kita Bangun; Romauli Pakpahan (Jurnal EduHealth, 2026)
Hospital is one of the health facilities where health efforts are carried out. Health efforts are every activity to maintain and improve health that aims to realize optimal health status for the community. Indonesian society currently requires quality health services based on five dimensions, namely tingible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee) and empathy (attention). The aim is to determine the effect of the quality of Hospital Pharmacy Installation services on the level of patient satisfaction at Hospital TK IV 01.07.01 Pematangsiantar from February - April 2025. This research method was conducted using a cross-sectional approach observation. The number of samples was 78 people with sampling techniques. The results of the study were analyzed with SPSS using the chi-square test. The results of the Cross Tabulation between the Effect of Pharmacy Service Quality on the Loyalty of General Outpatients at RS.Tentara in 2025 ρvalue 0.019 <0.05